Investigation of oxidative metabolism of uric acid and its role in redox processes in inflammation - Silva, Railmara Pereira da (2020)
This thesis studied the oxidation of uric acid during inflammation and its role in uric acid associated-pathologies . Uric acid is the end product of purine metabolism in humans and primates. Its concentration in plasma is higher than in other mammals, due to the repression of uricase gene. This repression was considered an evolutionary advantage since accumulation of uric acid in plasma increases the total blood antioxidant capacity. On the other hand, increased plasma uric acid has been associated with hypertension, gout, atherosclerosis and a worse prognosis in infection. Although the pathogenesis of these diseases is extremely complex and poorly understood, these associations suggest a causal role for uric acid. However, the exact mechanism for it is still unclear. Our group showed recently that uric acid is a substrate for myeloperoxidase, a heme-peroxidase abundant in neutrophils. The oxidation of uric acid by the enzyme generates urate free radical that combines with the radical anion superoxide to generate the oxidant urate hidroperoxide. Since chloride is the main substrate for myeloperoxidase, the present study aimed to investigate whether urate hidroperoxide would be formed during the oxidative burst in neutrophils. Through the sensitive liquid chromatography coupled to mass spectrometry method, we demonstrated the formation of urate hidroperoxide by peripheral blood neutrophils activated with phorbol miristate acetate, mimicking an inflammatory stimulus. Thus, we confirmed our hypothesis and demonstrated, for the first time, the formation of this new oxidant in inflammation. . The presence of uric acid during the inflammatory oxidative burst increased the oxidation of glutathione and the production of the radical anion superoxide, promoting a more oxidative environment. Besides the urate hydroperoxide, the oxidation of uric acid generates other intermediates that reactwith lysine residues to form covalent adducts in albumin, a process named uratylation.. These urate covalent adducts, as well as the end product of uric acid oxidation, allantoin, were elevated in plasma albumin from patients with heart failure and diabetes. Therefore, allantoin and uratylated peptides from albumin could be useful biomarkers of inflammatory and cardiovascular diseases. The oxidation of uric acid by neutrophils decreases the production of hypochlorous acid due to the competition between uric acid and chloride by myeloperoxidase and this hinders the microbicide activity of these cells against Pseudomonas aeruginosa, as previously demonstrated by our group. In the present study we demonstrated that the oxidation of uric acid is also more pronounced in patients with septicaemia. There was a significant augment of plasma allantoin and an uratylated peptide from albumin in these patients compared to health individuals. By incubating peripheral blood neutrophils with uric acid and Pseudomonas aeruginosa we detected in increase in allantoin, in the oxidation of glutathione and glutathionylation of the microbicide protein calprotectin (S100A8). Uric acid also increased total neutrophil triacylglycerols (TAGs), including those sterified with araquidonic acid. These data suggest that, in infectious processes, uric acid may indirectly affect protein function through the induction of glutathionylation and can also remodel lipid constitution in inflammatory cells. These alterations may have a relevant role in the pathogenesis of sepsis and could explain, at least in part, the worse correlation between sepsis and higher levels of plasma uric acid.In this context, we propose the assessment of allantoin and uratylated albumin peptides as useful tools to monitor the progression of infectious and inflammatory diseases